1992
DOI: 10.1266/jjg.67.463
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic study on sexual difference in emigration behavior of Drosophila melanogaster in a natural population.

Abstract: A quantitative genetic analysis was conducted on emigration response behavior using 140 second chromosome lines of Drosophila melanogaster. Fourteen sets of 5 x 5 partial diallel cross experiments were made in the parental generation. The emigration activity per batch of 50 male and 50 female F1 progeny was scored with Sakai's population system. Sexual difference did not appear in the emigration activity in these experiments. A significant genotype x sex x set interaction was detected. The genetic variance com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This finding is generally related to the particular sexual selection pressures and range size of focus species [13], [53], [54]. In Drosophila melanogaster , some authors have argued a sex-biased dispersal in favor of females from natural populations [55], [56] (but see [57]), that would comply with our observations of better female spatial learning. An alternative hypothesis is that Drosophila males and females could differ in their visual acuity, e.g.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is generally related to the particular sexual selection pressures and range size of focus species [13], [53], [54]. In Drosophila melanogaster , some authors have argued a sex-biased dispersal in favor of females from natural populations [55], [56] (but see [57]), that would comply with our observations of better female spatial learning. An alternative hypothesis is that Drosophila males and females could differ in their visual acuity, e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas we have yet to determine the specific components of a resource that inhibit the dispersal of males, our observation that males dispersed from food at a lower rate than females is consistent with previous findings for natural isolates tested at the optimum temperature for these flies (Iliadi et al. 2002; Mikasa and Narise 1980) (however, see Mckenzie 1974; Mikasa 1992). …”
Section: Discussionmentioning
confidence: 99%
“…Because molecules such as sex-peptides and others which are transmitted from male to female during copulation influence oviposition and remating of mated females (Chen and Bühler, 1970;Aigaki et al, 1991;Fuyama and Ueyama, 1997;Wolfner, 1997), I speculate that these molecules may mediate the decrease of emigration activity in mated females. Although it was suggested that the emigration activities of the sexes were under different genetic control (Mikasa, 1992), the factors derived from males from copulation may not be ignored with respect to the variability of emigration activity in the mated females. In this study, the females of every isofemale line in the mated group were mated with males of their own line to compare previous experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of genetic variance in emigration activity to the total variance were estimated in the female flies to be 33.0% (Mikasa, 1992) and 49.8% (calculated from the data of Mikasa and Narise [1986]). Those values and the values in the present study (27.4 and 53.0%) seemed to be within the same range, although different experimental conditions and different natural populations were used and the experimental data were too small for comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation